Potassium ion battery electrolyte and battery
By using linear carbonate main solvent, cyclic phosphate film-forming cosolvent and low viscosity additives in potassium ion batteries, the capacity attenuation and low conductance of potassium ion battery electrolyte is solved during the charging and discharge process. The rate problem achieves high conductivity and stable cycles, supports rapid discharge, and reduces costs.
Patent Information
- Application Number
- CN202411265149.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-13
AI Technical Summary
The existing potassium ion battery electrolyte has problems of capacity attenuation and low conductivity during charging and discharging, and cannot effectively exert the high energy density and high power potential of potassium ion batteries.
The electrolyte is used to combine linear carbonate main solvent, cyclic phosphate film-forming cosolvent and low viscosity additives, and combine high-purity potassium salts and additives to form a high conductivity electrolyte system for potassium ion batteries. Improve the interaction between potassium ions and anions and the generation of solid electrolyte interfaces, and reduce the viscosity of the electrolyte.
It realizes high conductivity and stable circulation of potassium ion batteries, with a maximum conductivity of up to 16.28mS cm-1, and the capacity retention rate at charge and discharge ratio exceeds 90%, supports rapid discharge, is low in cost and is suitable for large-scale production.
Smart Images

Figure CN119133612A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of potassium ion batteries, and in particular to a potassium ion battery electrolyte and a battery. Background Art
[0002] Lithium-ion batteries have the characteristics of high voltage, high energy density, and long cycle life, and have been widely used in portable electronic devices (mobile phones, laptops, etc.) and new energy vehicles. However, the uneven distribution and scarcity of lithium resources in the earth's crust limit the sustainable application of lithium-ion batteries, and also limit the application of lithium batteries in large-scale power storage. Potassium-ion batteries are considered to have great potential in the field of large-scale and low-cost electrochemical energy storage due to the rich reserves of potassium in the earth's crust, wide sources, and low cost. In addition, K + The standard electrode potential of the Li / K pair + The standard electrode potential of Li is similar to that of Li, and even higher than that of Li in non-aqueous electrolyte systems. + / Li is lower, theoretically has a higher output voltage. K + Compared with Li + The Lewis acidity is weaker and the solvation radius is smaller, which theoretically leads to a higher migration rate in the electrolyte, thus helping to realize higher power secondary batteries.
[0003] There are currently three main types of potassium ion battery electrolytes. One is a carbonate electrolyte based on traditional low-concentration potassium hexafluorophosphate (KPF6), ethylene carbonate (EC) and diethyl carbonate (DEC), but it will continue to decompose during the charge and discharge process, causing serious capacity decay. One is an ether electrolyte based on ethylene glycol dimethyl ether (DME). However, low-concentration DME electrolytes will cause co-embedding of K+ and solvent molecules on the graphite side, and the oxidation stability is poor, which greatly reduces the energy density of potassium ion batteries. There are also studies that use high concentrations and local high concentrations to inhibit the co-embedding of solvents on the graphite side and improve oxidation stability, but this will sacrifice the high conductivity of the electrolyte and greatly increase the cost. The third type is a phosphate electrolyte represented by trimethyl phosphate and triethyl phosphate. This type of electrolyte has good high-voltage stability and non-flammable properties, but the conductivity of this type of electrolyte is generally lower than the conductivity of the current commercial lithium-ion battery electrolyte, and it cannot give full play to the advantages of potassium ion batteries. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the prior art, maximize the advantages of potassium ion batteries from the perspective of electrolyte design, and provide a potassium ion battery electrolyte with high conductivity, stable carbon-based negative electrode and high voltage positive electrode, as well as a corresponding secondary battery, which takes into account low cost and high ionic conductivity while achieving stable circulation of potassium ion batteries.
[0005] The present invention adopts the following technical solution:
[0006] On the one hand, the present invention provides a potassium ion battery electrolyte, comprising a linear carbonate main solvent, a cyclic phosphate film-forming co-solvent, a low-viscosity additive and a potassium salt; wherein the volume fraction of the main solvent is 50 vol.% to 80 vol.%, the volume fraction of the film-forming co-solvent is 10 vol.% to 30 vol.%, and the volume fraction of the additive does not exceed 20 vol.%.
[0007] Any possible implementation as described above further provides an implementation, wherein the potassium salt is potassium bis(fluorosulfonyl)imide (KFSI), and the electrolyte concentration is 1.5 mol L -1 ~2mol L -1 ;
[0008] The main solvent is one of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), and methyl propyl carbonate;
[0009] The film-forming cosolvent is one of ethylene carbonate (EC), trimethylene carbonate, and propylene carbonate (PC);
[0010] The low viscosity additive is one of ethylene glycol dimethyl ether (DME), diethylene glycol dimethyl ether (G2), tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-MeTHF), 1,4-dioxane (1,4-DX), 1,3-dioxane (1,3-DX), 1,3-dioxolane (DOL), acetonitrile (AN), methyl acetate (MA), and ethyl acetate (EA).
[0011] Any possible implementation as described above further provides an implementation, wherein the potassium ion battery electrolyte also includes an additive, and the additive includes one of potassium hexafluorophosphate (KPF6), potassium bis(trifluorosulfonyl)imide (KTFSI), vinyl sulfate, vinyl sulfite, and tris(trimethylsilyl) phosphate; the mass fraction of the additive in the electrolyte does not exceed 5wt.%.
[0012] Any possible implementation as described above further provides an implementation, wherein the potassium salt, main solvent, film-forming co-solvent and additive are all analytically pure, with a purity of ≥99.5%, a moisture content of ≤50ppm, and other impurity ion content of less than 2ppm.
[0013] On the other hand, the present invention also provides a potassium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a diaphragm, and the potassium ion battery electrolyte as described above, wherein the diaphragm material is used to separate the positive electrode sheet and the negative electrode sheet.
[0014] Any possible implementation as described above further provides an implementation, wherein the potassium ion battery is a full cell or a half cell.
[0015] Any possible implementation as described above further provides an implementation, wherein the potassium ion battery is a button cell, a soft pack cell or a cylindrical cell.
[0016] Any possible implementation as described above further provides an implementation, when the potassium ion battery is a full battery, the positive electrode plate is composed of 60wt.% to 90wt.% of positive electrode material by mass fraction, 5wt.% to 20wt.% of conductive agent and 5wt.% to 20wt.% of first binder, the positive electrode material is potassium manganese iron based Prussian white material (K2MnFe(CN)6, KMF), and the mass fraction is the mass fraction relative to the total mass of the positive electrode;
[0017] The negative electrode plate is composed of 70wt.% to 95wt.% of negative electrode material, 0.5wt.% to 20wt.% of conductive agent and 0.5% to 10% of second binder. The negative electrode material is graphite or hard carbon. The mass fraction is the mass fraction relative to the total mass of the negative electrode.
[0018] According to any possible implementation described above, an implementation is further provided, wherein the first binder in the positive electrode plate is one of polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE); the second binder in the negative electrode plate is one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), sodium hydroxymethyl cellulose (CMC), and sodium alginate;
[0019] The conductive agent in the positive electrode sheet and the negative electrode sheet is one or more of acetylene black, Ketjen black, and carbon nanotubes;
[0020] The material of the diaphragm includes one of polyethylene (PE), polypropylene (PP) and glass fiber paper.
[0021] Any possible implementation as described above further provides an implementation, wherein when the potassium ion battery is a half-cell, the working electrode is one of Prussian white, graphite, and hard carbon, and the counter electrode and the reference electrode are both potassium metal.
[0022] The beneficial effects of the present invention are:
[0023] In the current research on electrolytes for potassium ion batteries, the solvation structure of the electrolyte is optimized by increasing the concentration of the electrolyte on the basis of traditional solvents, or a local high-concentration electrolyte is designed using a high-fluorinated ether, and a new solvent is used to replace the carbonate as the main solvent to achieve stable cyclic operation of the potassium ion battery. However, the above potassium ion battery electrolytes cannot provide higher conductivity, and the introduction of high-fluorinated ethers and high-concentration salts will increase the cost. In the electrolyte system provided by the present invention, the solvents used are all low-cost organic solvents, wherein the film-forming aid (such as EC) mainly functions to form a stable solid electrolyte interface (SEI) on the surface of the carbon-based negative electrode; the linear carbonate solvent used is a low-viscosity, weakly polar solvent, which mainly reduces the overall electrolyte viscosity, strengthens the interaction between potassium ions and anions, and allows more anions to participate in the formation of SEI; the low-viscosity additive further reduces the viscosity of the electrolyte while further improving the conductivity of the electrolyte. The maximum conductivity of the electrolyte system of the present invention can reach 16.28mS cm -1 Compared with traditional lithium-ion battery electrolyte (8-10mS cm -1 ) can be increased by nearly 2 times. The electrolyte system of the present invention is used in potassium ion batteries, which is more effective than using traditional electrolytes (1 mol L -1 KPF6 has better performance when dissolved in a mixed solvent of EC and DEC with a volume ratio of 1:1. -1 ) can be stably cycled for 100 weeks at a charge and discharge rate of 5C with almost no capacity decay (capacity retention rate>90%), while the potassium ion battery using traditional electrolyte has significant capacity decay after 100 cycles of charge and discharge (capacity retention rate<90%). In addition, the potassium ion battery using the electrolyte of the present invention also supports rapid discharge, and can maintain more than 75% of the 0.2C discharge capacity at a rapid discharge rate of 5C. The positive active material and the negative active material used in the present invention are simple to synthesize, and the electrolyte solvents used are all low-cost solvents, with low cost, simple preparation process, and convenient large-scale production, which has a very important prospect for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Shown is a schematic diagram of the ionic conductivity of the potassium ion battery electrolyte in Example 1, Example 2, Example 3 and Example 4 at room temperature.
[0025] Figure 2 The graphite-potassium half-cells in Examples 1, 2, 3 and 4 are shown in Figure 1 at room temperature, 0.2C (56mAg -1 ) schematic diagram of electrochemical performance under current density of a, Example 1; b, Example 2; c, Example 3; d, Example 4.
[0026] Figure 3 Shown are the first charge and discharge curves of the graphite-potassium half-cells in Examples 1, 2, 3 and 4.
[0027] Figure 4 The results are shown for the potassium-manganese-iron-based Prussian white-potassium half-cells in Examples 1, 2, 3 and 4 at room temperature, 0.2C (30 mA g -1 ) at a current density of : a, Example 1; b, Example 2; c, Example 3; d, Example 4.
[0028] Figure 5 The results are shown for the potassium-manganese-iron-based Prussian white-potassium half-cells in Examples 1, 2, 3 and 4 at room temperature, 0.2C (30 mA g -1 ) at a current density of .
[0029] Figure 6 The graph shows the potassium-manganese-iron-based Prussian white-graphite potassium ion battery in Example 1, Example 2, Example 3 and Example 4 at room temperature, 0.2C (30mA g -1 , schematic diagram of electrochemical performance under current density (relative to the mass of positive electrode active material): a, Example 1; b, Example 2; c, Example 3; d, Example 4.
[0030] Figure 7 The discharge rates (1C = 150 mA g) of the potassium-manganese-iron-based Prussian white-graphite potassium ion batteries in Example 1, Example 2, Example 3 and Example 4 are shown as follows: -1 ) under the charge and discharge curve. DETAILED DESCRIPTION
[0031] The specific embodiments of the present invention will be described in detail below in conjunction with specific drawings. It should be noted that the technical features or combinations of technical features described in the following embodiments should not be considered isolated, and they can be combined with each other to achieve better technical effects.
[0032] An embodiment of the present invention provides a potassium ion battery electrolyte, comprising a linear carbonate main solvent, a cyclic phosphate film-forming co-solvent, a low-viscosity additive and a potassium salt; wherein the volume fraction of the main solvent is 50 vol.% to 80 vol.%, the volume fraction of the film-forming co-solvent is 10 vol.% to 30 vol.%, and the volume fraction of the additive does not exceed 20 vol.%.
[0033] In a specific embodiment, the potassium salt is potassium bis(fluorosulfonyl)imide (KFSI), and the electrolyte concentration is 1.5 mol L -1~2mol L -1 ;
[0034] The main solvent is one of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), and methyl propyl carbonate;
[0035] The film-forming cosolvent is one of ethylene carbonate (EC), trimethylene carbonate, and propylene carbonate (PC);
[0036] The low viscosity additive is one of ethylene glycol dimethyl ether (DME), diethylene glycol dimethyl ether (G2), tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-MeTHF), 1,4-dioxane (1,4-DX), 1,3-dioxane (1,3-DX), 1,3-dioxolane (DOL), acetonitrile (AN), methyl acetate (MA), and ethyl acetate (EA).
[0037] In a specific embodiment, the potassium ion battery electrolyte also includes an additive, and the additive includes one of potassium hexafluorophosphate (KPF6), potassium bis(trifluorosulfonyl)imide (KTFSI), vinyl sulfate, vinyl sulfite, and tris(trimethylsilyl) phosphate; the additive accounts for no more than 5wt.% of the electrolyte mass fraction.
[0038] In a specific embodiment, the potassium salt, main solvent, film-forming co-solvent and additives are all analytically pure, with a purity of ≥99.5%, a moisture content of ≤50 ppm, and other impurity ion content less than 2 ppm.
[0039] A potassium ion battery according to an embodiment of the present invention comprises a positive electrode sheet, a negative electrode sheet, a separator, and the above-mentioned potassium ion battery electrolyte, wherein the separator is used to separate the positive electrode sheet and the negative electrode sheet to prevent the positive electrode sheet and the negative electrode sheet from directly contacting each other and causing a short circuit.
[0040] In a specific embodiment, the positive electrode material of the potassium ion battery is a potassium manganese iron-based Prussian white material, and the negative electrode material is a carbon-based negative electrode such as graphite and hard carbon.
[0041] In a specific embodiment, the mass ratio of the positive electrode potassium manganese iron-based Prussian white material is 60wt.% to 90wt.%, the mass ratio of the conductive carbon in the positive electrode sheet is 5wt.% to 20wt.%, and the mass ratio of the binder is 5wt.% to 20wt.%. The sum of the mass ratios of the conductive carbon, the binder and the positive electrode active material is ensured to be 1. The loading amount of the positive electrode active material can be controlled at 1mg / cm 2 ~10mg / cm 2 scope.
[0042] In a specific embodiment, the negative electrode active material in the negative electrode plate is a carbon-based material including graphite, hard carbon, soft carbon, etc., accounting for 70wt.% to 90wt.%, and the conductive carbon in the positive electrode plate accounts for 0.5wt.% to 20wt.%, and the binder accounts for 0.5wt.% to 10wt.%. Ensure that the sum of the mass ratios of the conductive carbon, the binder and the positive electrode active material is 1. The loading amount of the negative electrode active material can be controlled at 1mgcm -2 ~10mgcm -2 scope.
[0043] In a specific embodiment, in the potassium ion battery provided by the present invention, the capacity ratio of the negative electrode plate to the positive electrode plate can be controlled in the range of 1.1:1 to 1.2:1.
[0044] In a specific embodiment, the conductive carbon used in the positive electrode sheet and the negative electrode sheet can be one or more of acetylene black, Ketjen black and carbon nanotubes. The positive electrode sheet and the negative electrode sheet can use the same conductive carbon, or the positive electrode sheet and the negative electrode sheet can also use two different conductive carbons, which is not limited here.
[0045] In a specific embodiment, the first binder used in the positive electrode sheet is one of polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE), and the current collector is selected as aluminum foil.
[0046] In a specific embodiment, the binder used in the negative electrode sheet is one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), sodium hydroxymethyl cellulose (CMC), and sodium alginate, and the current collector can be one of aluminum foil or copper foil.
[0047] In a specific embodiment, the potassium ion battery separator can be selected from one of polyethylene (PE), polypropylene (PP), and glass fiber paper.
[0048] In a specific embodiment, the potassium ion battery provided by the present invention can be a button-type lithium ion battery, or can also be a soft-pack potassium ion battery.
[0049] In a specific embodiment, when the binder used in the battery pole piece is polyvinylidene fluoride (PVDF), the solvent used to prepare the slurry is N-methylpyrrolidone; when the binder used in the electrode pole piece is polytetrafluoroethylene (PTFE), the solvent used to prepare the slurry is isopropyl alcohol; when the binder used in the electrode pole piece is sodium carboxymethyl cellulose, the solvent used to prepare the slurry is water; when the binder used in the electrode pole piece is sodium alginate, the solvent used to prepare the slurry is water.
[0050] In a specific embodiment, during the preparation of the electrode slurry, there is no fixed ratio for the mixture of the solvent, the electrode material, the binder, and the conductive agent, as long as they are stirred evenly to form a slurry.
[0051] The specific implementation process of the present invention is described in detail below through specific embodiments, taking the preparation of button-type potassium ion batteries as an example.
[0052] Example 1
[0053] (1) Preparation of electrolyte: The following operations were performed in a glove box under an argon atmosphere: 876.9 mg of potassium bis(fluorosulfonyl)imide was weighed using a balance and dissolved in 1600 μL of ethyl methyl carbonate (EMC). 400 μL of ethylene carbonate (EC) was then added. A magnetic stirrer was added and stirred on a magnetic stirrer for 10 minutes. The mixture was allowed to stand for 6 hours to prepare a solution with a concentration of 2 mol L -1 KFSI EMC / EC (8 / 2) electrolyte. Then use a conductivity meter to test the ionic conductivity of the electrolyte at room temperature. Figure 1 The ionic conductivity of 2MKFSIEMC / EC 8 / 2 was shown to be 8.45 mS cm -1 .
[0054] (2) Preparation of positive and negative electrode sheets: Graphite was used as the negative electrode active material. The negative electrode active material and the binder CMC were mixed in a mass ratio of 9:1. After adding water and stirring evenly, the mixture was evenly coated on the carbon-coated aluminum foil current collector. After vacuum drying at 80°C, the negative electrode sheet was obtained. The loading amount of the negative electrode active material was 3 mg cm -2 Potassium manganese iron-based Prussian white was used as the positive electrode active material. The positive electrode active material, conductive carbon Ketjen black, and binder polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 8:1:1, N-methylpyrrolidone was added and stirred evenly, and then evenly coated on the carbon-coated aluminum foil current collector. After vacuum drying at 80°C, a positive electrode sheet was obtained. The loading amount of the positive electrode active material was 3 mg cm -2 .
[0055] (3) Preparation of half-cell: Use potassium metal as the counter electrode and glass fiber as the separator. In a glove box with water and oxygen content below 1 ppm, assemble button cells in the order of negative electrode shell, spring, gasket, potassium sheet, electrolyte, separator, electrolyte, negative (positive) electrode sheet, and positive electrode shell. After assembly, use a button cell sealing machine to compact the cell for subsequent testing. After the battery is assembled, let it stand for 5 hours, and use a battery testing system to perform constant current charge and discharge tests at room temperature. Figure 2 The graphite-potassium half-cell was shown to be able to charge at 0.2C (1C = 279 mA g) using 2M KFSI EMC / EC 8 / 2 electrolyte. -1) for 100 cycles at a current density of 2.5 % and a specific capacity of 271.7 mAh g -1 , the average Coulombic efficiency is 99.67%. Figure 3 The electrochemical curves of the first charge and discharge of the graphite-potassium half-cell are shown, and the coulombic efficiency of the first charge and discharge is 84.87%. Figure 4 The electrochemical performance of potassium manganese iron-based Prussian white-potassium half-cell was demonstrated at room temperature, 0.2C (1C = 155mA g -1 ) for 100 cycles at a current density of 1.35 W, and the discharge capacity was 127.6 mAh g -1 , the average Coulombic efficiency is 97.32%. Figure 5 The electrochemical curves of the first charge and discharge of the potassium-manganese-iron-based Prussian white-potassium half-cell are shown.
[0056] (4) Preparation of potassium ion battery: potassium manganese iron-based Prussian white as the positive electrode, graphite as the negative electrode, glass fiber as the separator, the mass ratio of positive electrode active material to negative electrode active material is 2:1, and button cells are assembled in the order of negative electrode shell, spring, gasket, negative electrode sheet, electrolyte, separator, electrolyte, positive electrode sheet, and positive electrode shell in a glove box with water and oxygen content less than 1ppm. After assembly, the battery is compacted using a button battery sealing machine for subsequent testing. After the battery is assembled, it is left to stand for 5 hours, and a constant current charge and discharge test is performed at room temperature using a battery testing system. Figure 6 The electrochemical performance of graphite-KMnFe-based Prussian potassium ion battery was demonstrated at 0.2C (1C = 155 mA g -1 ) can be stably cycled for 100 cycles with only a small amount of capacity decay, a capacity retention rate of 97.35%, and a discharge capacity of 136.7 mAh g -1 .
[0057] Example 2
[0058] (1) Preparation of electrolyte: The following operations were performed in a glove box under an argon atmosphere: 876.9 mg of potassium bis(fluorosulfonyl)imide was weighed using a balance and dissolved in 1200 μL of ethyl methyl carbonate (EMC), followed by the addition of 400 μL of ethylene carbonate (EC) and 400 μL of propylene carbonate (PC). A magnetic stirrer was added and the mixture was stirred on a magnetic stirrer for 10 minutes and allowed to stand for 6 hours to prepare a solution with a concentration of 2 mol L -1 KFSI EMC / EC / PC (6 / 2 / 2) electrolyte. Then use a conductivity meter to test the ionic conductivity of the electrolyte at room temperature. Figure 1 The ionic conductivity of 2M KFSI EMC / EC / PC6 / 2 / 2 is shown to be 10.69 mS cm -1 .
[0059] (2) The preparation process of the positive and negative electrode sheets is the same as that in Example 1.
[0060] (3) The half-cell preparation method was the same as in Example 1, and the electrolyte used was 2M KFSI EMC / EC / PC 6 / 2 / 2. Figure 2 Demonstrated that the graphite-potassium half-cell can achieve 0.2C (1C = 279mAg) at 2M KFSI EMC / EC / PC 6 / 2 / 2 electrolyte -1 ) for 100 cycles at a current density of 2.5 mAh g -1 , the average Coulombic efficiency is 99.71%. Figure 3 The electrochemical curves of the first charge and discharge of the graphite-potassium half-cell are shown, and the coulombic efficiency of the first charge and discharge is 83.33%. Figure 4 The electrochemical performance of potassium manganese iron-based Prussian white-potassium half-cell was demonstrated at room temperature, 0.2C (1C = 155mA g -1 ) for 100 cycles at a current density of 1.35 W, and the discharge capacity was 128.1 mAh g -1 , the average Coulombic efficiency is 96.79%. Figure 5 The electrochemical curves of the first charge and discharge of the potassium-manganese-iron-based Prussian white-potassium half-cell are shown.
[0061] (4) The preparation method of the potassium ion battery is the same as that in Example 1, and the electrolyte used is 2M KFSI EMC / EC / PC 6 / 2 / 2. Figure 6 The electrochemical performance of graphite-potassium manganese iron-based Prussian white potassium ion battery was demonstrated at 0.2C (1C = 155mA g -1 ) can be stably cycled for 100 cycles with almost no capacity decay, and the discharge capacity after cycling is 107.6 mAh g -1 .
[0062] Example 3
[0063] (1) Preparation of electrolyte: The following operations were performed in a glove box under an argon atmosphere: 876.9 mg of potassium bis(fluorosulfonyl)imide and 58.6 mg of potassium hexafluorophosphate were weighed using a balance and dissolved in 1000 μL of ethyl methyl carbonate (EMC). Then, 600 μL of ethylene carbonate (EC) and 400 μL of ethylene glycol dimethyl ether (DME) were added. A magnetic stirrer was added and the mixture was stirred on a magnetic stirrer for 10 minutes. The mixture was allowed to stand for 6 hours to prepare a solution with a concentration of 2 mol L -1 KFSI EMC / EC / DME (5 / 3 / 2) + 2wt.% KPF6 electrolyte. Then use a conductivity meter to test the ionic conductivity of the electrolyte at room temperature. Figure 1The ionic conductivity of 2M KFSI EMC / EC / DME5 / 3 / 2 is shown to be 13.21 mS cm -1 .
[0064] (2) The preparation process of the positive and negative electrode sheets is the same as that in Example 1.
[0065] (3) The half-cell preparation method was the same as in Example 1, and the electrolyte used was 2M KFSI EMC / EC / DME 5 / 3 / 2. Figure 2 The graphite-potassium half-cell was shown to be able to operate at 0.2C (1C = 279 mA g) using 2M KFSI EMC / EC / DME 5 / 3 / 2 electrolyte. -1 ) for 100 cycles at a current density of 2.5 mAh g -1 , the average Coulombic efficiency is 99.75%. Figure 3 The electrochemical curves of the first charge and discharge of the graphite-potassium half-cell are shown, and the coulombic efficiency of the first charge and discharge is 83.82%. Figure 4 The electrochemical performance of potassium manganese iron based Prussian white-potassium half-cell is demonstrated. At room temperature, 0.2C (1C = 155mAg -1 ) for 100 cycles at a current density of 1.3 mAh g -1 , the average Coulombic efficiency is 97.37%. Figure 5 The electrochemical curves of the first charge and discharge of the potassium-manganese-iron-based Prussian white-potassium half-cell are shown.
[0066] (4) The preparation method of the potassium ion battery is the same as that in Example 1, and the electrolyte used is 2M KFSI EMC / EC / DME 5 / 3 / 2. Figure 6 The electrochemical performance of graphite-potassium manganese iron-based Prussian white potassium ion battery was demonstrated at 0.2C (1C = 155mA g -1 ) can be stably cycled for 100 cycles with almost no capacity decay, and the discharge capacity after cycling is 110.5 mAh g -1 .
[0067] Example 4
[0068] (1) Preparation of electrolyte: The following operations were performed in a glove box under an argon atmosphere: 876.9 mg of potassium bis(fluorosulfonyl)imide and 58.6 mg of potassium hexafluorophosphate were weighed using a balance and dissolved in 1000 μL of dimethyl carbonate (DMC). Then, 600 μL of ethylene carbonate (EC) and 400 μL of ethylene glycol dimethyl ether (DME) were added. A magnetic stirrer was added and the mixture was stirred on a magnetic stirrer for 10 minutes. The mixture was allowed to stand for 6 hours to prepare a solution with a concentration of 2 mol L -1KFSIDMC / EC / DME (5 / 3 / 2) + 2wt.% KPF6 electrolyte. Then use a conductivity meter to test the ionic conductivity of the electrolyte at room temperature. Figure 1 The ionic conductivity of 2M KFSIDMC / EC / DME5 / 3 / 2 was shown to be 16.28 mS cm -1 .
[0069] (2) The preparation process of the positive and negative electrode sheets is the same as that in Example 1.
[0070] (3) The half-cell preparation method was the same as in Example 1, and the electrolyte used was 2M KFSIDMC / EC / DME 5 / 3 / 2. Figure 2 The graphite-potassium half-cell was shown to be able to charge at 0.2C (1C = 279 mAg) using a 2M KFSIDMC / EC / DME 5 / 3 / 2 electrolyte. -1 ) for 100 cycles at a current density of 2.5 Å / min, and the specific capacity is 271.4 mAh g -1 , the average Coulombic efficiency is 99.70%. Figure 3 The electrochemical curves of the first charge and discharge of the graphite-potassium half-cell are shown, and the coulombic efficiency of the first charge and discharge is 82.91%. Figure 4 The electrochemical performance of potassium manganese iron-based Prussian white-potassium half-cell was demonstrated at room temperature, 0.2C (1C = 155mA g -1 ) for 100 cycles at a current density of 1.5 200 mAh g -1 , the average Coulombic efficiency is 96.34%. Figure 5 The electrochemical curves of the first charge and discharge of the potassium-manganese-iron-based Prussian white-potassium half-cell are shown.
[0071] (4) The preparation method of the potassium ion battery is the same as that in Example 1, and the electrolyte used is 2M KFSIDMC / EC / DME 5 / 3 / 2. Figure 6 The electrochemical performance of graphite-potassium manganese iron-based Prussian white potassium ion battery was demonstrated at 0.2C (1C = 155mA g -1 ) can be stably cycled for 100 cycles with almost no capacity decay, and the discharge capacity after cycling is 113.6 mAh g -1 . Figure 7 The rapid discharge capability of graphite-potassium manganese iron-based Prussian white potassium ion battery was demonstrated at discharge rates of 0.2C, 0.5C, 1C, 2C, 3C, 4C, and 5C (1C = 150mA g -1 ) can release 108.1, 104.5, 101.3, 96.6, 88.8, 83.7, and 82.6 mAh g respectively. -1 The specific capacity has good rate performance.
[0072] The maximum conductivity of the electrolyte system of the present invention can reach 16.28mS cm -1 Compared with traditional lithium-ion battery electrolyte (8-10mS cm -1 ) can be increased by nearly 2 times. The electrolyte system of the present invention is used in potassium ion batteries, which is more effective than using traditional electrolytes (1 mol L -1 KPF6 is dissolved in a mixed solvent of EC and DEC with a volume ratio of 1:1) and has better performance. Taking Examples 1-4 as an example, in the graphite-potassium half-cell, the first charge and discharge efficiency of Examples 1-4 is >80%, while that of the conventional electrolyte is only 74%; in the potassium-manganese-iron-based Prussian white-potassium half-cell, the discharge specific capacity of Example 4 can reach 140mAh g -1 The average coulombic efficiency is >95%, while the discharge capacity in traditional electrolyte is less than 100 mAh g -1 , Coulombic efficiency <80%; in KMnFe-based Prussian white-graphite cells at 0.2C (30 mA g -1 ) can be stably cycled for 100 weeks at a charge and discharge rate of 5C with almost no capacity decay (capacity retention rate>90%), while the potassium ion battery using the traditional electrolyte has significant capacity decay after 100 cycles of charge and discharge (capacity retention rate<90%). In addition, the potassium ion battery using the electrolyte of the present invention also supports fast discharge, and can maintain more than 75% of the 0.2C discharge capacity at a fast discharge rate of 5C.
[0073] Although several embodiments of the present invention have been given herein, those skilled in the art should understand that the embodiments of the present invention may be modified without departing from the spirit of the present invention. The above embodiments are merely exemplary and should not be used as a limitation on the scope of the present invention.
Claims
1. A potassium ion battery electrolyte, characterized in that The potassium ion battery electrolyte comprises a linear carbonate main solvent, a cyclic phosphate film-forming auxiliary solvent, a low-viscosity auxiliary agent and a potassium salt; wherein the volume fraction of the main solvent is 50 vol.% to 80 vol.%, the volume fraction of the film-forming auxiliary solvent is 10 vol.% to 30 vol.%, and the volume fraction of the low-viscosity auxiliary agent does not exceed 20 vol.%.
2. The potassium ion battery electrolyte according to claim 1, wherein The potassium salt is potassium bis(fluorosulfonyl)imide, and the electrolyte concentration is 1.5 mol L -1 ~2mol L -1 ; The main solvent is one of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate and methyl propyl carbonate; The film-forming cosolvent is one of ethylene carbonate, trimethylene carbonate and propylene carbonate; The low viscosity additive is one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, 1,4-dioxane, 1,3-dioxane, acetonitrile, methyl acetate, and ethyl acetate.
3. The potassium ion battery electrolyte according to claim 1, wherein The potassium ion battery electrolyte also includes an additive, which includes one of potassium hexafluorophosphate, potassium bis(trifluorosulfonyl)imide, vinyl sulfate, vinyl sulfite, and tris(trimethylsilyl)phosphate; the additive accounts for no more than 5wt.% of the electrolyte mass fraction.
4. The potassium ion battery electrolyte according to claim 3, wherein The potassium salt, main solvent, film-forming auxiliary solvent and additives are all analytically pure, with a purity of ≥99.5%, a moisture content of ≤50ppm, and other impurity ion contents less than 2ppm.
5. A potassium ion battery, characterized in that: The potassium ion battery comprises a positive electrode sheet, a negative electrode sheet, a separator, and a potassium ion battery electrolyte as described in any one of claims 1 to 4, wherein the separator is used to separate the positive electrode sheet and the negative electrode sheet.
6. The potassium ion battery according to claim 5, characterized in that The potassium ion battery is a full battery or a half battery.
7. The potassium ion battery according to claim 5, characterized in that The potassium ion battery is a button cell, a soft pack cell or a cylindrical cell.
8. The potassium ion battery according to claim 6, characterized in that When the potassium ion battery is a full battery, the positive electrode plate is composed of 60wt.% to 90wt.% of positive electrode material, 5wt.% to 20wt.% of conductive agent and 5wt.% to 20wt.% of first binder by mass fraction, the positive electrode material is potassium manganese iron based Prussian white material, and the mass fraction is the mass fraction relative to the total mass of the positive electrode; The negative electrode plate is composed of 70wt.% to 95wt.% of negative electrode material, 0.5wt.% to 20wt.% of conductive agent and 0.5% to 10% of second binder. The negative electrode material is graphite or hard carbon. The mass fraction is the mass fraction relative to the total mass of the negative electrode.
9. The potassium ion battery according to claim 8, characterized in that The first binder in the positive electrode plate is one of polyvinylidene fluoride and polytetrafluoroethylene; the second binder in the negative electrode plate is one of polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol, sodium hydroxymethyl cellulose, and sodium alginate; The conductive agent in the positive electrode sheet and the negative electrode sheet is one or more of acetylene black, Ketjen black, and carbon nanotubes; The material of the separator includes one of polyethylene, polypropylene and glass fiber paper.
10. The potassium ion battery according to claim 6, characterized in that: When the potassium ion battery is a half-cell, the working electrode is one of Prussian white, graphite, and hard carbon, and the counter electrode and the reference electrode are both potassium metal.
